2018
DOI: 10.1002/anie.201707333
|View full text |Cite
|
Sign up to set email alerts
|

The Ideal Ionic Liquid Salt Bridge for the Direct Determination of Gibbs Energies of Transfer of Single Ions, Part I: The Concept

Abstract: Described is a procedure for the thermodynamically rigorous, experimental determination of the Gibbs energy of transfer of single ions between solvents. The method is based on potential difference measurements between two electrochemical half cells with different solvents connected by an ideal ionic liquid salt bridge (ILSB). Discussed are the specific requirements for the IL with regard to the procedure, thus ensuring that the liquid junction potentials (LJP) at both ends of the ILSB are mostly canceled. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 16 publications
0
25
0
2
Order By: Relevance
“…One of the biggest problems of potentiometry is the unknown potential drop at the liquid junction, called liquid junction potential (Anon, 2019). Recently, it was shown that liquid junction potentials of even different solvents cancel out (Ermantraut et al, 2018;Radtke et al, 2018) if an almost ideal ionic liquid is used. This means that we do not have to measure or estimate the liquid junction potential in our experiments if we use the ionic liquid mentioned in the reference.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the biggest problems of potentiometry is the unknown potential drop at the liquid junction, called liquid junction potential (Anon, 2019). Recently, it was shown that liquid junction potentials of even different solvents cancel out (Ermantraut et al, 2018;Radtke et al, 2018) if an almost ideal ionic liquid is used. This means that we do not have to measure or estimate the liquid junction potential in our experiments if we use the ionic liquid mentioned in the reference.…”
Section: Introductionmentioning
confidence: 99%
“…However, all unified acidities have been measured in non-aqueous systems only with rather special metal solidcontact glass electrode half-cells (Beliustin et al, 1992) until now. The work on unified pH started with metal solid-contact electrodes, because these electrodes performed better in water than other electrodes that were tested (Suu, 2013), and similar glass electrodes filled with mercury worked well in DMSO (Koppel et al, 1977;Kütt et al, 2008). These electrodes give stable and reproducible signals in non-aqueous solvents and their mixtures with water.…”
Section: Introductionmentioning
confidence: 99%
“…Although this was among the best we have tried [10,15,28,32], and was recently confirmed by Lindner et al [20], there must be many better alternatives in view of the tuned mobilities of the IL-constituent cation and anion, the solubility in water, the environmentally friendliness, etc. For bridging an aqueous solution and an organic phase, Krossing's group proposed a new IL consisting of cation and anion having nearly equal mobilities and successfully used it to minimize the liquid junction potential across the aqueous-organic boundary [6,26].…”
Section: Ionic Liquid Salt Bridge: Present Situation and Future Possimentioning
confidence: 99%
“…Zuvor allerdings erläutern wir ein sehr ernstzunehmendes Problem der Einzelionenthermodynamik. Aktuelle Arbeiten lassen aber darauf schließen, dass es eine Lösung dafür geben könnte …”
Section: Arbeiten Mit Der Vereinheitlichten Aziditätsskalaunclassified
“…Aktuelle eigene Arbeiten zielen auf eine Annahme‐freie Methode, die sich “ideale” Salzbrücken mit ionischen Flüssigkeiten (Ionic‐Liquid Salt‐Bridge, ILSB) in “Solvatationszellen” zunutze macht. In diesem Kontext bedeutet für 1:1‐Elektrolyte “Idealität” die Gleichheit der Diffusionskoeffizienten oder Überführungszahlen von Kation und Anion in der reinen IL als auch in den untersuchten Lösungsmitteln.…”
Section: Arbeiten Mit Der Vereinheitlichten Aziditätsskalaunclassified